The Expressionist figure the Miriam and Erwin Kelen Collection of Drawings - Rothfuss, Joan 1953- (Walker Art Center, 2019)
"The Expressionist Figure' documents a collection amassed over more than 60 years and recently gifted to the Walker, which includes some 80 superlative works on paper that focus on the figure. Dating from 1900 to 2018, the drawings span more than a century of artistic experimentation in the US and Europe and were executed in mediums ranging from graphite, ink and crayon to pastel, gouache and collage. Among the artists represented are Milton Avery, Max Beckmann, Christo, Chuck Close, Edgar Degas, Willem de Kooning, Otto Dix, Marlene Dumas, Arshile Gorky, David Hockney, Jasper Johns, William Kentridge, Ernst Ludwig Kirchner, Paul Klee, Gustav Klimt, René Magritte, Henri Matisse, Joan Miró, Claes Oldenburg, Pablo Picasso, Sigmar Polke, Egon Schiele, Ben Shahn, Zak Smith and Andy Warhol. Published on the occasion of the first exhibition of this collection, this luxurious volume includes full-page color reproductions of each drawing along with a catalog entry detailing the history of each object. Also included are an essay by the collector on his passion for drawing, and curator Joan Rothfuss' deeply researched short essays on 14 individual works. Both beautiful and substantive, 'The Expressionist Figure' is a testament to the pleasure of building a collection and the rewards of sharing it."--Publisher's description
Auf der Rückseite des Titelblatts: "Published on the occasion of the exhibition "The Expressionist Figure: The Miriam and Erwin Kelen Collection of Drawings", curated by Joan Rothfuss and organized by the Walker Art Center, Minneapolis. Walker Art Center, Minneapolis November 17, 2019-April 19, 2020"
Keywords: The Miriam and Erwin Kelen Collection of Drawings; Geschichte 1907-2019; Geschichte 1900-1930; Mensch -- Motiv; Expressionismus; Zeichnung; Human figure in art / Exhibitions; Drawing / 19th century / Exhibitions; Drawing / 20th century / Exhibitions; Expressionism (Art) / Exhibitions; Drawing; Expressionism (Art); Human figure in art; 1800-1999; Exhibition catalogs; Ausstellungskatalog -- Walker Art Center -- 17.11.2019-19.04.2020 -- Minneapolis, Minn.; Bildband